ŚAṄKARADEVA AND SATTRIYA DANCE OF ASSAM A STUDY ON DIFFERENT DANCES OF AṄKῙYĀ NĀṬ - Sonowal, Bornali; Goswami, Madhurima (International Journal of Research -GRANTHAALAYAH, 2025)
Sattriya, a living dance tradition of the North-east India, Assam, is deeply embedded in the spiritual and cultural fabric of the region. The saint and reformer Srimanta Śaṅkaradeva erected the Sattriya dance as a medium for disseminating the teachings of Vaishnavism through performance arts. This paper explores the historical genesis and evolution of Sattriya, tracing its transformation from a ritualistic practice to a recognized classical dance form. It also examines the socio-religious context of the contributions of Śaṅkaradeva and Madhavdeva, the structure and role of sattras, and the stylistic features that define the dance. Drawing on archival sources and field studies this research underscores Sattriya’s enduring relevance and its contribution to India’s cultural heritage.